PENGUJIAN MUTU FISIK FORMULASI SEDIAAN SABUN PADAT BERBAHAN SUSU KEDELAI - Sanjiwani, Ni Made Sukma Sanjiwani; Ni Nyoman Yudianti Mendra; Agus Sudharmayasa (Program Studi Pendidikan Matematika dan Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2024)
Soap is a product formed through the reaction between fatty acids and strong bases, which has a function as a dirt cleaner. Soap containing Sodium Lauryl Sulfate (SLS) can cause irritation for users with sensitive skin types. The use of natural ingredients is highly considered to minimize the side effects of using synthetics. Soy milk is one of the natural ingredients that can be utilized because it contains antioxidant compounds that are beneficial to ward off free radicals on the skin. Soy milk also contains saponin compounds, a natural ingredient used as a soap foaming agent that is more environmentally friendly than chemicals. This study aims to evaluate the physical quality of soy milk solid soap dosage formulations. In this study, four soap formulas were made with variations in soy milk concentrations of 11, 15 and 19%. The physical quality test parameters included organoleptic test, homogeneity test, pH test, and foam height test. The research data was analyzed with SPSS version 25 with the Kruskal-Wallis test with a confidence level of 95%. Based on the results of the study, soy milk solid soap was obtained with good physical quality including organoleptic, homogeneity and foam height. However, the pH value of soy milk solid soap does not comply with the provisions imposed for soap products.